Public perceptions of polygenic testing and embryo selection for non-medical traits - Edmond Awad; Clara Colombatto; Joanna Demaree-Cotton; Brian D. Earp; Jim A. C. Everett; Peng Liu; G. Owen Schaefer; Ilina Singh; Dominic Wilkinson; Julian Savulescu (Nature Human Behaviour, 2026)
Abstract Some advances in reproductive technologies raise substantial ethical and psychological challenges, for example, the use of preimplantation genetic testing to select embryos based on non-medical traits. While studies have explored public willingness to use preimplantation genetic testing for medical or non-medical attributes, stated willingness may not reflect implantation decisions when such information is available. This large cross-national study examined public views on polygenic embryo testing. In a US sample ( N = 1,467), participants were more willing to test for medical conditions (for example, heart disease) than non-medical traits (for example, antisocial behaviour or low intelligence), although over half supported testing for non-medical traits. In a forced-choice implantation task, participants used medical and non-medical information to a similar extent when making decisions. Similar patterns were observed in Chinese participants ( N = 623). These findings suggest variability in choices across specific traits and conditions, rather than a uniform distinction between medical conditions and non-medical traits. The Stage 1 protocol for this Registered Report was accepted in principle on 7 October 2025. The protocol, as accepted by the journal, can be found at https://osf.io/vb9c2 .